2017
DOI: 10.1016/j.jpcs.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure lattice-dynamics of NdVO4

Abstract: High-pressure Raman-scattering measurements and ab initio calculations on NdVO4 have been carried out up to 30 GPa. Our combined experimental and theoretical study confirms that beyond 5.9 GPa NdVO4 undergoes an irreversible zircon to monazite transition. The coexistence of zircon and monazite phases is experimentally observed up to ~ 8 GPa (which agrees with the theoretical transition pressure), stabilizing the monazite phase as a single phase around 10 GPa. Calculations additionally predict the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 56 publications
6
30
2
Order By: Relevance
“…Afterwards, we will focus on the influence of pressure on the absorptions related to Nd 3+ . These results will be correlated with the information known on the HP behavior of the crystal structure and Raman modes of NdVO4 [13][14][15][16]. The first phenomenon we observe is that the absorption edge gradually blue-shifts from ambient pressure to 4.7 GPa.…”
Section: High-pressure Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…Afterwards, we will focus on the influence of pressure on the absorptions related to Nd 3+ . These results will be correlated with the information known on the HP behavior of the crystal structure and Raman modes of NdVO4 [13][14][15][16]. The first phenomenon we observe is that the absorption edge gradually blue-shifts from ambient pressure to 4.7 GPa.…”
Section: High-pressure Studiessupporting
confidence: 82%
“…A second focus of research on NdVO 4 has been the influence of pressure on its properties and crystal structure. Numerous studies have been carried out, reporting the existence of a phase transition around 5-6 GPa [13][14][15][16]. Interestingly, it has been found that the crystal structure of the high-pressure (HP) phase strongly depends on the conditions of the experiment (namely, hydrostatic or non-hydrostatic conditions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symmetry annotations were made in accordance with the previous assignments reported in the literature. 10,11,27 Fig. 6 shows the UV-Vis diffuse reflectance spectrum of the NdVO 4 nanoneedles prepared in this study.…”
Section: Raman Analysismentioning
confidence: 99%
“…Under an applied pressure of about 6 GPa, Dragomir and Valant: Room-Temperature Synthesis and Optical Properties ... the zircon-type NdVO 4 undergoes a phase transformation to a metastable monazite-type structure with the space group P2 1 /n (Z = 4) where the Nd atoms are located in a eight-coordinate site (with eight unique Nd−O bond distances). 10,11 At around 11.4 GPa, NdVO 4 further transforms to a scheelite-type phase and so to a denser packing. All these phase transformations are accompanied by a decrease of the band gap by 0.5 eV (measured on a single crystal).…”
Section: Introductionmentioning
confidence: 99%